Perspective of Muhammadiyah Education Institutions on the Dynamics of Multicultural Islamic Education - Muryadi, Muryadi; Astutik, Astutik; Warisno, Andi; Andari, An An; Anshori, M Afif (Graduate Program Magister Manajemen Pendidikan, 2023)
The conceptual purpose of this article is to reveal the dynamics of multicultural Islamic education from the perspective of Muhammadiyah educational institutions. A qualitative writing method with a historiographical approach to reveal cultural history, cultural practices and explanations of the cultural texts of the Muhammadiyah educational institution. The findings of this conceptual research on multicultural Islamic education are the disclosure of the dynamics of the Muhammadiyah institution which has a moderate Islamic style seen from the attitude values instilled in cadres, students and students in each educational institution it manages. Multicultural values are instilled through al-Islam and Muhammadiyah subjects as a characteristic of Muhammadiyah education, which is different from other educational institutions. Because this subject is characteristic, it becomes an